2012
DOI: 10.2131/jts.37.565
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effects for dietary exposure of bisphenol A during <i>in utero</i> and lactational periods on reproductive development in rat offspring

Abstract: The potential for health effects on humans with exposure to bisphenol A (BPA) has raised concerns, and the adverse effects of low-dose exposure to BPA on reproduction have been controversial. The purpose of the present study was to investigate the effects of low-dose exposure to BPA on reproductive development in F(1) rat offspring. Pregnant female Sprague-Dawley rats (F(0)) were fed a diet containing low doses of BPA (0, 0.33, 3.3, or 33 ppm) from gestational day (GD) 6 through postnatal day (PND) 21. The wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 48 publications
(49 reference statements)
3
28
0
Order By: Relevance
“…No effect was seen on male AGDs, whereas AGDs were significantly shorter in 1-month-old females exposed to 0.17 and 1.7 mg/kg, but not at 3 months of age. As the effects were only seen in the younger females, the authors did not consider the results to be biologically significant (Kobayashi et al 2012). However, these reductions in female AGDs corroborate the findings from this study, and it is possible that measurement of AGD in newborn male and female rats, instead of 1-and 3-month-old rats, would have yielded some even more similar results to the present ones.…”
Section: Discussionsupporting
confidence: 71%
“…No effect was seen on male AGDs, whereas AGDs were significantly shorter in 1-month-old females exposed to 0.17 and 1.7 mg/kg, but not at 3 months of age. As the effects were only seen in the younger females, the authors did not consider the results to be biologically significant (Kobayashi et al 2012). However, these reductions in female AGDs corroborate the findings from this study, and it is possible that measurement of AGD in newborn male and female rats, instead of 1-and 3-month-old rats, would have yielded some even more similar results to the present ones.…”
Section: Discussionsupporting
confidence: 71%
“…In females, perinatal exposure to BPA increased the number of terminal end buds in mammary tissues of CD-1 mice exposed to estradiol later in life without affecting the terminal end buds in mammary tissues of C57BL/6 mice [22]. Furthermore, BPA increased the weight of offspring born to gestationally exposed ICR and adult CD1 Swiss mice, decreased the weight of offspring born to neonatally exposed ICR mice, but did not affect the weight of offspring born to gestationally and neonatally exposed C57BL/6J mice [15,[38][39][40]. Although timing of exposure may also play a role in birth weight following exposure to BPA, future studies should directly compare BPA effects in various strains to account for other potential confounders.…”
Section: Discussionmentioning
confidence: 90%
“…Although some effects such as disrupted uterine implantation and pregnancy maintenance are supported by strong evidence [3][4][5][6][7][8], other effects such as the effects on steroidogenesis are only partially supported by existing data [4,6,[9][10][11][12][13][14][15]. The ambiguity of these studies may be due to the study design, specifically the strain of animal used in the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive toxicology studies have established no-observedadverse-effect-levels (NOAELs) ranging from 5 to 50 mg/kg/day, further reinforcing the significance of first pass metabolism for mitigating BPA's potential risk (Ema et al, 2001;Tyl et al, 2002Tyl et al, , 2008Howdeshell et al, 2008;Ryan et al, 2010;Kobayashi et al, 2010Kobayashi et al, , 2012Stump et al, 2010). Delclos et al (2014) and Churchwell et al (2014) reported reproductive effects in rat pups after gavage dosing of dams from gestational day 6 and subsequent gavage dosing of pups from PND1 with 100 and 300 mg/kg/day BPA but not with dosages of 2.7 mg/kg/day or lower.…”
Section: Introductionmentioning
confidence: 98%